Outlaws still at large! a saga of roots country music since the 1970s - Hamilton, Neil A. 1949- (Outlaw Press, 2013)
"The first-ever book to cover the history of the renegade Outlaw country music movement from its beginnings in the 1970s to its resurgence today, "Outlaws Still At Large!" draws from the author's interviews with current artists to reveal a rich, vibrant music scene beneath the mainstream Nashville gloss, while it shows the trials and adventures of life on the road. Hamilton traveled more than 20,000 miles with the Outlaws to get his story, and in the end, the music changed his life" ... Amazon.com